Green bonds as an innovative sovereign financial instrument - Wiśniewski, Marcin; Zieliński, Jakub (Ekonomia i Prawo. Economics and Law, 2019)
Motivation: There is a growing awareness of the impact that climate change is having on the world economy and the standards of living. Green bonds (GBs) are relatively new and innovative instruments on the financial market where the capitals are also invested in projects that generate environmental or climate benefits. The newness of this financial instrument could be the main reason behind the scarcity of scientific publications on green bonds; thus, it remains an undeveloped research area. One of the problems is also classifying securities as GBs. Therefore, it is exceedingly important to distinguish labelled green bonds and unlabelled climate-aligned bonds. Aim: In the article, the authors will present the evolution of the green bonds market and attempt to assess the observed and potential effects of green bonds’ issuances, taking into account governments issues. Results: Green bonds are the next stage of market growth. In the article, the authors will present the benefits of green bonds and the positive impact that their issuance has on the issuer and on investors’ image as socially responsible entities. Therefore, strong investor demand can lead to oversubscription. Thus, green bonds could be one of the easiest ways to attract investors and potentially increase issuance size which can contribute to lower costs of financing green public tasks.